Internet connectivity disruption in Pakistan (Pakistan) - Voidly (2026)
CRITICAL severity mixed detected in Pakistan. Confidence: 65%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: PK-2026-0138
Keywords: censorship; PK; mixed; critical